The standardised evaluation of training participants in religious training center - Rizal Hatapayo (Balai Diklat Keagamaan Ambon, 2022)
This research conducted to provide a standardized description of the systematic grading evaluation of participants in the trainings held by the Religious Education and Training Centers at the Ministry of Religion. Systematic Literature Review method was used to review the related literature followed by conclusions based on implementation instructions from valid sources. The results showed that the evaluation techniques and instruments had been provided, yet the indicators for each rating scale need to be provided to assist the assessment process. Thus, it is necessary to make a standard grading rubric for all Religious Education and Training Centers. This also will help them measuring the success of a training.